Advances in Cryptology - EUROCRYPT 2006 25th International Conference on the Theory and Applications of Cryptographic Techniques, St. Petersburg, Russia, May 28 - June 1, 2006, Proceedings - Vaudenay, Serge (Security and Cryptology ;, 2006)
The 2006 edition of the Eurocrypt conference was held in St. Petersburg,Russia from May 28 to June 1, 2006. It was the 25th Eurocrypt conference. Eurocrypt is sponsored by the International Association for Cryptologic Research (IACR). Eurocrypt2006waschairedbyAnatolyLebedev,andIhadtheprivilegetochair the Program Committee. Eurocrypt collected 198 submissions on November 21, 2005. The Program Committee carried out a thorough review process. In total, 863 review reports were written by renowned experts, Program Committee members as well as external referees. Online discussions led to 1,114 additional discussion messages and about 1,000 emails. The review process was run using e-mail and the iChair software by Thomas Baign` eres and Matthieu Finiasz. Every submitted paper received at least three review reports. The Program Committee had a meeting in Lausanne on February 4, 2006. We selected 33 papers, noti?ed acceptance or rejection to the authors, and had a cheese fondue. Authors were then invited to revise their submission. The present proceedings include all the revised papers. Due to time constraints the revised versions could not be reviewed again. We delivered a "Eurocrypt Best Paper Award." The purpose of the award is to formally acknowledge authors of outstanding papers and to recognize - cellence in the cryptographic research ?elds. Committee members were invited to nominate papers for this award. A poll then yielded a clear majority. This year, we were pleased to deliver the Eurocrypt Best Paper Award to Phong Q.